The impact of COVID-19 on HIV care: a comprehensive analysis of patient and healthcare providers experiences at the largest HIV treatment center in Ghana - Peter Puplampu; Justice K. Baah; Karl Osei Afoduo; Bright A. Adjei; Araba Abaidoo-Myles; Victor G. Davila-Roman; George B. Kyei; Collins S. Ahorlu (BMC Health Services Research)
Abstract Background We sought to determine how the COVID-19 pandemic affected care delivery for HIV patients in Ghana. Methods Guided by the Consolidated Framework for Implementation Research (CFIR), we performed a cross-sectional study between May and July 2021 among 40 people living with HIV and 19 healthcare providers caring for HIV patients. In-depth interviews and focus group discussions were done with HIV patients, doctors, nurses, pharmacists, laboratory scientists, data scientists, administrators, and counselors to ascertain barriers and facilitators to HIV care during the pandemic. We asked for their input on removing barriers to care during this and future pandemics. Data was analyzed thematically with the help of the qualitative software MAXQDA. Results Pre-pandemic practices, such as using cards for appointments and making phone calls to patients, and intra-pandemic measures, such as re-arranging the clinic setup for patient safety, contributed to clinic attendance. However, the fear of infection, transportation costs, and fear of stigma impeded clinic attendance. Patients spent less time in the clinic because stable patients received medication refills without seeing the doctor. This meant many patients with chronic diseases like hypertension, diabetes, and hyperlipidemia did not get the necessary physician review during the pandemic's peak. Due to pervasive stigma, patients were cautious about home delivery of medications and telemedicine solutions. Conclusion While solutions like telemedicine and home visits may work for primary care or other chronic conditions during pandemics, stigma makes these interventions unattractive options for many HIV patients.